The Growth Of Lettuce (Lactuca sativa) Hydroponically In Simple Wick System On Various Types Of Nutrient Composition - Nyayu Siti Khodijah; Riwan Kusmiadi (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2021)
The supply of hydroponic nutrients needs to consider economic, practical and resource saving aspects. It is necessary to know the best composition and type of nutrients that can be used in a hydroponic system. The use of liquid organic fertilizers (POC) as an alternative to hydroponic nutrients, especially in the wick system, has already begun including widely available alternative fertilizers such as NPK + Gandasil and utilizing chicken feather waste that has been made in the form of fertilizer. This research is expected to provide an overview of the potential for alternative nutrient sources for hydroponic growing media by utilizing the available resources. The study was started from June to August 2020, using a single randomized block design (RBD) consisting of 5 (five) treatment levels, namely: K0 = AB mix (control) 50 ml / 10 L water, K10 = 10 g NPK + 5g Gandasil / 10L water. K11 = 1/2 dose of Abmix + ½ dose of NPK + Gandasil, K12 = ½ dose of NPK + Gandasil + 4800ml / POC of chicken feathers / 10L of water, K13 = 1/2 dose of Abmix + 4800ml / POC of chicken feathers / 10L of water. The results showed that the type of nutrient media composition had no significant effect on plant height in weeks 1,2,3 and 4, leaf length weeks 1 and 2 and number of leaves weeks 1,2,3 and 4. The type of nutrient media composition had a significant effect on leaf length weeks. 3rd and 4th week.The best treatment was obtained at K0. (Abmix), which was significantly different from k10 and k12 treatments, and not significantly different from all k11 and 13 treatments.At week 4, the best leaf length was also obtained at different k0 treatments. real with all other treatments. There is potential for alternative nutrient utilization, because it is able to approach growth using standard nutrients for variables of plant height and leaf number.